Proposing new body mass index and waist circumference cut-offs based on cardiometabolic risks for a Central Asia population: A feasibility study - Kali, Aknur; Gusmanov, Arnur; Aripov, Marat; Chan, Mei-Yen (Frontiers in Endocrinology, 2022)
Background Lower BMI cutoffs as compared to standard cut-offs have been recommended to reduce the risk of obesity-related co-morbidities in some ethnic populations (e.g. south Asian and Chinese populations). Recent attempts have also been made to establish ethnicity-specific BMI cutoffs to identify individuals affected with obesity in relation to type 2 diabetes risk in multi-ethnic populations based in the UK and North America. However, to date, there is yet to have any published work done to identify these cut-offs in Central Asia populations nor specify any difference for genders even though the fat distribution varies amongst the different ethnic groups as well as between the genders. To the best of the authors’ knowledge, this is the first study exploring new BMI and WC cut-offs in this population. Methods To address this gap, we used a database of secondary care electronic health records from the National Research Cardiac Surgery Center to identify BMI and waist circumference cutoffs for obesity based on the risk of developing diabetes and other cardiometabolic disorders among 297 adults in Kazakhstan. Bivariate and multivariable logistic regression analysis were utilized to investigate the relationships between risk factors and type 2 diabetes mellitus (T2DM). BMI and WC thresholds were predicted using the Youden index. Results For an equivalent age-adjusted and sex-adjusted incidence of type 2 diabetes at a BMI of 30·0 kg/m2 in White populations, we found higher BMI cutoffs for Kazakhstani women (30.5 kg/m2) but lower cut-offs for men (28·9 kg/m2). As for waist circumference, the cut-off points for females were 95cm and 104 cm for males. Conclusions For Central Asia populations, the current recommended BMI and WC cutoffs may not be suitable and further work is needed to establish specific cut-offs for this population.